Nonclonal Chromosomal Aberrations in Childhood Leukemia Survivors - Chin, Tong Foh; Ibrahim, Kamariah; Thirunavakarasu, Tharshanadevasheri; Azanan, Mohamad Shafiq; Oh, Lixian; Lum, Su Han; Yap, Tsiao Yi; Ariffin, Hany (Taylor & Francis, 2018)
Background: Survivors of childhood cancer are at risk of developing a second malignancy. One possible mechanism for neoplastic transformation of cells is through induction of persistent genomic instability. This study aims to seek evidence of chromosomal instability in long-term childhood leukemia survivors (CLS) in one of the largest pediatric academic oncology centers in South East Asia. Methods: 50 asymptomatic (subjects have remained leukemia-free since treatment cessation) CLS and 50 healthy controls were recruited in this cross-sectional study. Of 50 CLS, 44 had acute lymphoblastic leukemia and 6 had acute myeloid leukemia. G-banded karyotyping was performed on unstimulated peripheral blood leukocytes of all subjects. Results: CLS had significantly higher occurrence of karyotypic abnormalities compared to controls. Five CLS harbored six nonclonal abnormalities (mostly aneuploidy) while none were found in controls. Conclusion: Subpopulations with nonclonal chromosomal aberrations were present in peripheral blood leukocytes of our cohort of childhood leukemia long-term survivors.